Redesign of a Virtual Jet Pump Laboratory for Higher Process Engineering Education - Terkowsky, Claudius; Boettcher, Konrad; Grünendahl, Sabrina; Brandner, Dean (International Journal of Online and Biomedical Engineering (iJOE), 2025)
The digital transformation increasingly requires the development of competencies for learning and working in the context of Industry 4.0. To meet this need, a practical action research project was conducted to design and implement a virtual instructional laboratory for fluid mechanics in a higher process engineering education course. This paper provides a detailed overview of the key steps and outcomes of the project, including the design of a virtual jet pump experiment using a game engine, the implementation of a real-world scenario (RWS) that was developed with a special constructive alignment (CA) checklist for instructional design of laboratory learning, and the corresponding empirical investigation. The findings demonstrate that the integrated approach employed in this project can enhance learning outcomes related to competencies required in the Industry 4.0 work environment, despite the challenges encountered by students in mastering the RWS. This paper concludes by exploring some potential future directions for further work in the field.